Performative Revolution in Egypt An Essay in Cultural Power - Alexander, Jeffrey C. (Bloomsbury Academic, 2011)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Jeffrey C. Alexander examines what was new about Egypt's Spring revolution. Why was it so compelling to watch, and what made it so effective and does it have implications for democratic movements internationally. Using international news reports and translations of the social media pages that brought Egyptians flocking onto Tahrir Square, Alexander uncovers the narrative of a revolution that was scripted by its organizers, as both a moral statement and a media and digital statement. He sees it as a theatrical performance, designed to reveal to the key protagonists what a civil, egalitarian society might look like, by showing it in microcosm on the Square. Ultimately, he argues, it was the sight of the protestor's behaviour that swayed the army, and brought about regime change. From the author of the widely acclaimed 2010 book: The Performance of Politics: Obama's Victory and the Democratic Struggle for Power, this powerful intervention into the debate on the Arab Spring is a must-read for those curious about how social media are fundamentally changing global politics.